Regulating Terrorism Before the Act of Terror: A comparative study (Strathmore Law Journal, 2020)
In light of the growing risks that terrorism presents to civilised society, Western governments have adopted a broad range of laws and administrative regulations designed to thwart terrorists before they can commit acts of terror. Beyond mere conspiracy or attempt, these laws have sought to proscribe activity that exists as a stand-alone offence but that acts as a proxy for the sorts of offences that constitute true terror activity. This article serves to examine these various approaches. It groups these approaches into four categories: prohibitions on membership in terror organisations; intangible support to terror organisations; restrictions on travel to areas that have terror groups operating openly; and money laundering and other financial crimes tied to the financing of terror organisations. It then identifies a single example within each group to use as a case study to explore the contours of the specific approach, while tying the example to larger trends within Western countries’ legal systems. Finally, this article considers the implications for countries considering adopting one or more of these approaches, including the ways that multiple approaches can work in tandem. The article does not make specific recommendations, but rather recognises that each country’s government must consider the benefits and costs of adopting these approaches carefully and with an eye to both its security and its society.